Downsizing Harshness Framework: Wage Cuts or Layoffs in a Collaborative Context? - Arney Einarsdottir; Katrin Olafsdottir (Nordic Journal of Working Life Studies, 2025)
The Nordic labor markets are characterized by high levels of trust, social, and employment security where tripartite collaboration is a cornerstone. When organizations are hit by a crisis, management needs to seriously consider what alternatives exist to downsize the labor force. In this study, we develop a framework of downsizing harshness, by classifying downsizing alternatives as soft, moderate, or hard. We then explore the application of downsizing alternatives during an economy-wide recession in a flexible and collaborative Nordic labor market, focusing on the hard alternatives, layoffs, and wage cuts. Data was collected from HR managers in Iceland at two points in time after the economy was hit by a deep recession in 2008, and probit regressions are used for analysis. Findings show that organizations were more likely to implement nominal wage cuts than layoffs and mass layoffs were rarely used in isolation. Furthermore, decision-making gravitated toward harsher alternatives as the recession continued.